A framework of leadership sustainability rating system (LSRS) for future construction project managers - Akhavan Tabassi, Amin; Abdullah, Aldrin; Argyropoulou, Maria; M. Roufechaei, Kmanad; Argyropoulou, Rachel (International Journal of Engineering and Technology, 2018)
The construction industry continues to be viewed as inevitable in encouraging societal, economic, and environmental improvements for development of sustainability in a world-wide context. The research on project management for green construction are mostly focused on project level. So far, there has been no framework for rating project leader’s competencies in the context of sustainable construction. The aim of this paper is to propose a framework for rating leaders’ competencies in integrating and promoting the sustainability practices when managing green construction projects. Based on a review on Sustainable Building Development, this study relates the dimensions of leadership with the Seen, Lean and Green sustainability concepts. As a result, an organizational-level Leadership Sustainability Rating System has been developed for the future of the industry. The approach revealed ten leadership competencies for sustainable leaders, and thirteen fundamental practices to be followed for sustainable development. The value of the framework lies in its ability to be used in parallel with the Sustainable Building Rating Systems offering thus a holistic method to examine the performance of the building from its early stages when leaders take technical and managerial decisions that require to be put in place and communicated to all project stakeholders.
Keywords: Project management; Sustainability; Leadership; Construction Industry; Malaysia.